2020
DOI: 10.1111/jasp.12693
|View full text |Cite
|
Sign up to set email alerts
|

“Change my selfie”: Relationships between self‐objectification and selfie‐behavior in young Italian women

Abstract: Self‐objectification is a pervasive phenomenon, related to specific socio‐cultural context, that can lead to many psychological and interpersonal consequences. With the present study, we investigated the correlates of self‐objectification in young Italian women analyzing both its traditional antecedents and its consequences for self‐presentation on social network sites (SNS). A total of 676 Italian university female students completed a self‐reported questionnaire on self‐objectification, internalization of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 88 publications
(161 reference statements)
1
14
0
Order By: Relevance
“…Young adult women with selfie behavior may be more likely to engage in body surveillance and as a result experience body image disturbance (Butkowski et al, 2019). Higher frequency of posting selfies was associated with trait selfobjectification (Bell et al, 2018;Caso et al, 2020) and can predicted increases in self-objectification (Wang et al, 2019). Thus, selfie behavior may foster self-objectification and plays a critical role in shaping individuals' attitudes towards their bodies, including increasing body surveillance and body shame.…”
Section: Discussionmentioning
confidence: 99%
“…Young adult women with selfie behavior may be more likely to engage in body surveillance and as a result experience body image disturbance (Butkowski et al, 2019). Higher frequency of posting selfies was associated with trait selfobjectification (Bell et al, 2018;Caso et al, 2020) and can predicted increases in self-objectification (Wang et al, 2019). Thus, selfie behavior may foster self-objectification and plays a critical role in shaping individuals' attitudes towards their bodies, including increasing body surveillance and body shame.…”
Section: Discussionmentioning
confidence: 99%
“…Effectively, social media using ARF have been accused by an increasing number of studies to promote "Snapchat dysmorphia" [9], a particular occurrence of body dysmorphic disorders (BDD), consisting in a misalignment between the desired image of one's body and the one actually perceived, due to continuous and intensive use of beautification ARF [10,11]. In turn, Snapchat dysmorphia would lead to lower levels of self-esteem [12] and higher levels of depression [13][14][15]; to several disorders of nutritional behaviour [16] and more frequent use of plastic surgery [17][18][19]; to selfobjectification [20,21] and adaptation to stereotypical socio-cultural aesthetic standards [22] (including racial and skin-colours ones [23]); to "aesthetic labour" [24] and mutual surveillance through female "policing gazes" [25]. However, other studies have shown that beautification is neither the only reason for the use of ARFs nor the prevailing one; in fact, aesthetic motivations are flanked by entertainment, coolness, curiosity, social interaction, silliness, having fun, creativity, brand "fandomship" and so on [26][27][28][29].…”
Section: Arf As Assemblagesmentioning
confidence: 99%
“…In addition, it has been shown that women, generally, report higher levels of dietary restraint than men ( Conner and Armitage, 2002 ; Wardle et al, 2000 ), which in turn has been associated to media pressure, thin-ideal internalisation, and body dissatisfaction ( Chang et al, 2013 ; Kong et al, 2013 ). In fact, women, compared to men, have a greater tendency to internalise cultural body standards ( Boursier et al, 2020 ; Caso et al, 2020 ; Gioia et al, 2020 ), in particular the thin-ideal.…”
Section: Introductionmentioning
confidence: 99%